Influence of Age and Body Mass Index ( BMI) in Estimation of Glomerular Filtration Rate (GFR) in Healthy Adults - Sharmin, Samira; Rahman, Md Mahbub Ur; Begum, Hosne Ara; Siddique, Md Abu Bakker; Uddin, Md Monir; Ferdous, Jasmine; Mutsuddy, Pupree; Yasmin, Farida (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: Obesity is a major health problem which has clinically significant role to develop kidney disease. This study was performed to see the association between Body Mass Index (BMI) and glomerular filtration rate ( GFR) in healthy adults. Patients and methods: This cross sectional study was carried out at Institute of Nuclear Medicine and Allied Sciences, Mitford, Dhaka, over a period of 12 months from January 2014 to December 2014. A total 34 adult healthy person (prospective kidney donor) who underwent 99mTc Di-ethylene triamine penta acetic acid (DTPA) renogram with camera Gated GFR was studied to find out the relationship between BMI and GRF as well as age and GFR. Pearson’s correlation coefficient and multiple regression analysis were done to see the relationship Results: This study included 34 healthy adults. Among them 09 (26.5%) were female and 25 (73.5%) were male. Mean age was 46.82±11.68 years (range 27 to 65 years), mean BMI was 22.76±4.06 kg/m2 (range 15 to 33 kg/m2), mean weight was 53.76±9.6 kg (range 33 to 71 kg), mean height was 152±7.8 cm (range 140 cm to 175 cm), mean GFR was 82.38±22.26 ml/min (range 41.2 to 131.15 ml/min), mean serum creatinine level was 0.92±0.20 mg/dl (range 0.57 to 1.40 mg/dl). Pearson correlation coefficient test showed that inverse relationship (r= -0.340, P= 0.049) exist between age and GFR whereas a positive (r= 0.425, P= 0.012) relationship exist between BMI and GFR and also with weight (r= 0.354, P=0.040). Multiple regression analysis showed that BMI (β =0.376,P=0.029) and age ( β=-0.185,P=0.04) were independent predictors for GFR ( both P < 0.05) but not with serum creatinine ( β= -0.176,P=0.296) and sex (β= 0.135,P=0.399). Conclusion: The findings of the study showed that GFR had a positive correlation with BMI and inverse relationship with age. Bangladesh J. Nuclear Med. 19(1): 15-18, January 2016